2013
DOI: 10.2351/1.4811838
|View full text |Cite
|
Sign up to set email alerts
|

Use of track/layer morphology to develop functional parts by selective laser melting

Abstract: Selective laser melting (SLM) is a powder-based additive manufacturing capable to produce parts layer-by-layer from a 3D computer-aided design model. Currently, there is a growing interest in industry for applying this technology for generating objects with high geometrical complexity. To introduce SLM process into industry for manufacturing real components, excellent mechanical properties and high functionality of final product must be achieved. Properties of the manufactured parts depend strongly on each sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 22 publications
2
40
1
4
Order By: Relevance
“…Previous studies in the field of laser beam modulation have shown the possibility of obtaining uniform temperature fields in the heating zone with the use of Flat-top and Inverse Gaussian laser beam power density distribution [13]. Many scientists in their papers have mentioned nearly the same set of SLM process parameters including twelve positions associated with laser beam, gas atmosphere and powder parameters [14,15].…”
Section: Problem Statementmentioning
confidence: 99%
“…Previous studies in the field of laser beam modulation have shown the possibility of obtaining uniform temperature fields in the heating zone with the use of Flat-top and Inverse Gaussian laser beam power density distribution [13]. Many scientists in their papers have mentioned nearly the same set of SLM process parameters including twelve positions associated with laser beam, gas atmosphere and powder parameters [14,15].…”
Section: Problem Statementmentioning
confidence: 99%
“…Selective laser melting (SLM), as a newly developed direct digital manufacturing technology, has been treated as one of the most effective powder-based additive manufacturing (AM) methods for metal parts. [10][11][12][13][14][15][16][17] During SLM process, the 3D parts are built by selectively fusing and consolidation of the thin layers of powder using the high-energy laser beam in a layer-by-layer manner according to the computeraided design (CAD) models of the parts. Because of the unique processing mechanisms of SLM, e.g., a full melting of powder materials followed by a rapid solidification at a rate up to10 6 -10 8 K/s, 18 the molten materials tend to experience a particular nonequilibrium metallurgical process during SLM processing, thereby providing a capacity to produce unique aluminum-based nanocomposite parts.…”
Section: Journal Of Laser Applications Laser Additive Manufacturing Fmentioning
confidence: 99%
“…В изделиях, полученных по технологии селек-тивного лазерного плавления, помимо специфич-ной структуры могут присутствовать дефекты -главным образом это микротрещины и поры [2,[13][14][15][16][17][18]. Последние разделяют на два основных вида.…”
Section: Introductionunclassified
“…Поры второго типа оказывают значительно большее влияние на механические свойства мате-риала вследствие их большего размера, а также пло-ской формы [13][14][15][16][17][18]. Для уменьшения пористости в конечных изделиях ответственного назначения применяется горячее изостатическое прессование, во многих случаях позволяющее существенно по-высить качество изделий после СЛП [19].…”
Section: Introductionunclassified